A dangerous world implicit theory: examining overlap with other criminogenic constructs. Issue 1 (2nd January 2021) - Ildeniz, Gaye; Ó Ciardha, Caoilte
ABSTRACT: Ward and Keenan (1999, Child molesters' implicit theories. Journal of Interpersonal Violence, 14(8), 821–838. doi: 10.1177/088626099014008003) hypothesised that some individuals who sexually offend against children have belief systems through which they perceive the world as an inherently dangerous place – labelled a dangerous world implicit theory (DWIT). Individuals with a DWIT are hypothesised to either (1) believe it is necessary to punish women and/or children who are perceived as threatening, or (2) see children as more accepting than adults, and as capable of understanding and gratifying the individual's needs and desires. In two online studies ( N  = 113 and N  = 123) we examined the possible overlap between the DWIT and four other constructs: hostile attribution bias, hostile sexism, emotional congruence with children, and a 'children as sexual beings' implicit theory. Results suggest that identifying with an individual holding DWIT overlaps considerably with some of the other constructs, but not with hostile attribution bias – a finding that ran counter to our hypotheses.